La falta de normativa legal, como generadora de violación de los derechos constitucionales de los comerciantes informales en el Ecuador. - ANTONIO GÓMEZ, EDGAR (2011)
In the Ecuador, there are approximately 3'0000. 000 Ecuadorians who survive and maintain their families through informal trade or freelance work, i.e. in activities which are not under dependent relationship, developing all kinds of livelihood strategies where globalization and labour flexibility, have led to unemployment and unprotected, all this without any kind of social benefits Despite the fact that there are constitutional rules that it provides and guarantees. In the Latin American context, informal commerce has similar characteristics in their causes and effects is not in the treatment of the phenomenon, because confluence of factors specific to each region, political situations, ideologies, and percentages of informality, etc., but if there is a common factor in most cases, is brutal and permanent repression towards this broad sector of the economy of the States. In the Ecuador, despite the fact that there are rules that regulate and protect the rights of informal traders, they are not met mostly because there are ambiguities in these rules, and deficiency of secondary rules that specify, facilitate and efectivicen those rights. The end result is that almost nearly three years of adoption of the Magna Carta, informal traders, per live and remains as if there were no rules and fundamental rights that cover them. The results that have emerged in the development of this research should serve to improve the quality of life of Ecuadorian informal traders, whereas there are considerations of a social legal nature, related to the effective enjoyment of the rights which attend them, more protection and social security, which must be tried to this majority labour social sector. This research work envisages some reforms, which have been implemented in the international context, but with the particularity that have been adapted to the Ecuadorian reality.